Rapamycin Attenuates High Glucose-Induced Inflammation Through Modulation of mTOR/NF-κB Pathways in Macrophages - Dai, Jiezhi; Jiang, Chaoyin; Chen, Hua; Chai, Yimin (Frontiers in Pharmacology, 2019)
Background: NLRP3 inflammasome is one of the key contributors to the impaired wound healing in diabetes. In this study, we assessed the role of rapamycin on high glucose-induced inflammation in THP-1-derived macrophages and investigated the underlying signaling mechanisms. Methods: THP-1-derived macrophages were treated with high glucose to induce NLRP3 inflammasome activation. The cells were pretreated with rapamycin, BAY 11-7082 or PDTC before exposure to HG. mTOR, NF-κB and NLRP3 inflammasome expression were measured by western blot. Results: In our experiment, we found rapamycin reduces NLRP3 inflammasome activation in macrophages. Rapamycin reduced NLRP3 inflammasome activation by inhibiting mTOR phosphorylation and NF-κB activation. Moreover, mTOR siRNA inhibited NF-κB activation, leading to the suppression of NLRP3 inflammasome activation. Conclusion: Rapamycin could ameliorate high glucose-induced NLRP3 inflammasome activation by attenuating the mTOR/NF-κB signaling pathway in macrophages. Rapamycin might act as a possible therapeutic option for high glucose-induced inflammatory response in impaired wound healing in the future.